PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PADA BADAN LAYANAN UMUM DAERAH PENGELOLAAN AIR LIMBAH DOMESTIK (BLUD PALD) KOTA BEKASI - Edward Efendi Silalahi; Siti Nurmayanti (Juremi: Jurnal Riset Ekonomi, 2023)
This study aims to determine whether there is an effect of workload and compensation on employee performance at the Badan Layanan Umum Daerah Pengelolaan Air Limbah Domestik Kota Bekasi, either partially or simultaneously. This study uses quantitative methods, where primary data is obtained from the distribution of questionnaires. The population in this study were all employees of the Badan Layanan Umum Daerah Pengelolaan Air Limbah Domestik Kota Bekasi, totaling 63 employees, and the sample taken by all employees was 63 people, the technique used was saturated sampling. Saturated sampling is a sampling technique where all members of the population are used as samples, other terms are saturated samples or censuses. The results showed that partially the workload variable had a positive and significant effect on employee performance. Partially, the compensation variable has a positive and significant effect on employee performance. And simultaneously Workload and Compensation have a positive and significant effect on Employee Performance at the Badan Layanan Umum Daerah Pengelolaan Air Limbah Domestik (BLUD PALD) Kota Bekasi